Pengaruh Media Accordion-Book dan Pop Up Book terhadap Pengetahuan Pencegahan Anemia Remaja - Pibriyanti, Kartika; Putri, Ashifa Purnama; Rooiqoh, Qothrunnadaa Fajr; Fathimah, Fathimah (ARTERI : Jurnal Ilmu Kesehatan, 2024)
Anemia screening conducted by Puskesmas Kendal in February 2023 showed an anemia prevalence of 50%. The results were obtained from 716 students in grades VII and X, with a description of 135 mild anemia, 153 moderate anemia, and 12 severe anemia. Screening results at SMA 1 Kendal 62.2% of adolescent girls showed low hemoglobin levels (anemia). This is thought to be due to a lack of understanding of the information obtained from health promotion by local health workers or other media that affects the lifestyle and diet of adolescents in meeting their daily needs. This study aims to determine the effect of accordion and pop-up books on adolescents' knowledge about anemia prevention. This study used the quasi-experiment method with a pretest-posttest design with a control group in two groups. Sampling was done using the purposive sampling technique, and the total sample was 112 adolescents. Data analysis was done using the Wilcoxon test and the Mann-Whitney test. The average value of knowledge before and after being given knowledge about anemia prevention with accordion book media is 75.00 increasing to 95.00, while pop-up book media is 70.00 increasing to 95.00. The results showed an effect of accordion book educational media on knowledge of preventing anemia in adolescents, as evidenced by a p-value of 0.000. There is an effect of pop-up book educational media on anemia prevention knowledge in adolescents, as evidenced by a p-value of 0.000. The most effective media for increasing adolescents' knowledge about anemia is a pop-up book, with a difference value of 25. The conclusion is that accordion books and pop-up book media have an effect on increasing adolescents’ knowledge about anemia prevention, and pop-up book educational media is more effective.